Inspection and challenges of new technologies - Vicente Mora Baringo (ADIDE Federación, 2008)
Two challenges are presented on the educational ground and, consequently, both affect the Inspectorate of Education. On one side, schools are undertaking an innovation process -which involves all the people with interest on education- that includes school management, the relationship with students' families and the interaction with students themselves, who happen to live naturally on a digital sphere. On the other hand, an Act of Parliament for the regulation of digital proceedings has been recently passed. With the support of new technologies, it intends to produce a new type of administration which gets over the everlasting drawbacks of time and space that discourage citizens when trying to access to it, and allows them to fulfil all the necessary requirements in a procedure.